Local scale fracture characterization of an advanced structured material manufactured by fused deposition modeling in 3D printing. (Fracture and Structural Integrity, 2019)
Additive manufacturing (AM) is a promising way to produce complex structures by adding layers. It arises great interest both in industrial and academic sectors to develop new advanced structured material. To benefit from its advantages, it is important to accurately characterize the obtained structures in order to ensure their integrity during operation. It becomes then important to characterize these structures at the local scale (micron and/or the nanometer scale). In the specific case of polymeric materials obtained by Fused Deposition Modeling (FDM), the comprehension of the mechanical behavior between adjacent layers during deformation can help improving mechanical properties. However, few studies in the literature have focused on implementing approaches to characterize local strains at the surface of these materials. In this study, an original approach based on the use of speckle pattern with particle average size of 20 microns in diameter was coupled to digital image correlation (DIC). It has been applied to the case of a SENT structure with a notch made by FDM. The successive images recorded by a digital microscope allow a qualitative analysis of the evolutions of the local strains. The kinematic fields are obtained by DIC. The strain evolutions at the tip of the notch are highlighted. The deformation mechanisms at the local scale are confronted with macroscopic behavior of the structure.
Keywords: Additive manufacturing; 3D printing; Digital Image Correlation; Micro speckle; Fracture mechanics